Análisis de riesgo crediticio y su incidencia en la liquidez de las Cooperativas de ahorro y crédito del segmento 3 de la ciudad de Latacunga, provincia de Cotopaxi período 2017 – 2018. - Pallo Cuchiparte, Willian Rodrigo (2019)
The research project presents information regarding credit risks and liquidity, in order to establish the problems that result from credit partner’s obligations by various internal factors such as: late payment and field monitoring, external factors like: the stability of the country and labor, causing the over-indebtedness of the partners. The main objective is to analyze the credit risk and its impact on the liquidity of Cooperativas of savings and credit Andina Ltda and Sumak Kawsay of segment 3 at Latacunga City of Cotopaxi province period 2017 - 2018, applying financial indicators to determine the monitoring and control of it. For the execution of the research project it was necessary to apply researching instruments such as the interview for both the Manager and the Headmaster of credit, as well as a prior analysis to the Financial Statements over 2017 and 2018 of the Savings and Credit Cooperatives where a research was made of credit portfolios that each entity has, in this way the defaulting and liquidity percentages could be verified. For which methods such as field research, documentary research and bibliography have been used, in this way relevant information was obtained for the research project, in such a way that it could be concluded that the credit risk is presented by several factors. internal and external affecting the liquidity of the Cooperatives since it is a solvency factor for the development of the same, thus reaching the objectives and goals set for the development of the investigation. At the end of the project it was possible to determine that the portfolios of overdue loans and defaulting produce uncertainty for credit recovery, which in turn affects the liquidity of the Cooperatives.